PEMENUHAN HAK DAN KEWAJIBAN SUAMIISTRI PENYANDANG DISABILITAS DI DESA TUMBAL KECAMATAN COMAL KABUPATEN PEMALANG PERSPEKTIF MAQA>S}ID AL-SYARI>’AH - Khasanah, Uswatun (Al-Hukkam: Journal of Islamic Family Law, 2023)
Person with disabilities who have married certainly will not be separated from their right and obligations as husband and wife. They still have to carry out their obligations as married couple in general. But in fact persons with disabilities in the Village of Tumbal, Comal Sub-district, Pemalang District who have married have difficully in currying out the life of a household ark. Based on this reality, the formulation of the problem in this study is 1) what are the positive efforts made by persons with disabilities in fulfilling the right and obligation of husband and wife in Tumbal Village, Comal District, Pemalang Regency? 2) How to ful fill the right and obligations of husband and wife with disabilities in Tumbal Village, Comal District, Pemalang Regency maqa>s}id al-Syari>’ah perspective?. This study aims to determine the positive efforts made by persons with disabilities in ful filling the right and obligations of husband and wife in Tumbal Village, Comal District, Pemalang Regency and explain the maqa>s}id al-Syari>’ah Perspective on the ful fillment of the rights and obligations of husband and wife with disabilities in Tumbal Village, Comal District, Pemalang Regency. This research is a type of field reseach using a qualitative approach. The location of this research is ini Tumbal Villagge, Comal District, Pemalang Regency, with the subject of married couples with disabilities. Data sources in the form of primary data and secondary data, for primary data collection using interview and observation techniques, while secondary data with documentation techniques. Data analysis refers to the interactive model of Miles Huberman. The results of the study show that people with disbailities in a effort to ful fill their marital rights and obligations are no different from families in general. The effort they make to help each other in carryng out the obligations of husband and wife are actions that bring mas}lahah or goodness to them and to their domestic life. The mas}lahah category is included in the mas{lahah al-Hajiyyah category, namely secondary mas}lahah, which is needed by humans to make life easier and eliminate difficulties and limitations. Overall, the benefits embodied in ful filling family obligations for persons with disabilities are in line with the fulfillment of the objectives of Islamic law in maintaining all aspects of mas}lahah in maqa>s}id al-Syari>’ah, namely hifz} al-Di>n, hifz} al-‘Aql, hifz} an-Nafs, hifz} an-Nasl dan hifz} al-Ma>l.